Еfficiency of floating coating for fire protection of wooden buildings - Bondarenko, O.; Tsapko, Yu.; Tsapko, O.; Kaverin К.; Lialina, N.; Semigran, D. (Ways to Improve Construction Efficiency, 2024)
Studies of the effect of wood flame retardant on ignition have established the parameters of flame propagation and combustion suppression, which makes it possible to influence this process. It is proved that they consist in creating a layer on the surface of the material, which prevents heating to a critical temperature, when intensive decomposition begins with the release of the required amount of flammable gases and their ignition. This makes it possible to determine the effect of fire protection and the properties of protective compositions on the process of inhibiting the rate of wood burning. During the tests of wood samples it was found that the untreated sample took 52 s, the flame spread throughout the sample for 100 s instead, the sample fire-retardant "FIREWALL-ATTIK" did not catch fire, impregnating solution ВС-13 and "FIREWALL-SV-1", Namely a mixture of 271.1 g/m2, took 570 and 560 s, the spread of flame on the surface occurred only in the first areas, the maximum flue gas temperature was 86 and 89 °C for more than 5 times, and the flammability index decreased to 4. For the sample protected by "FIREWALL-LAC" ignition occurred at the last second, the flame was recorded at level 0. For the sample fire-protected by "FIREWALL-WOOD" coating no ignition occurred, combustibility index 0. Due to this, it became possible to determine the conditions for changing the parameters of combustion and braking in fire protection of wood by forming a barrier to thermal conductivity. The results of comparing the experimental data of wood burning rate with the obtained analytical equations showed the correspondence between them. Thus, there is reason to argue about the possibility of targeted regulation of fire protection processes of wood by using fire-retardant coatings capable of forming a protective layer on the surface of the material, which inhibits the rate of wood burning.